Helping patients to understand their medicines. Issue 6 (16th June 2022) - Thompson, Angus
Abstract : Spending time in conversation with patients helps them to become well informed and active participants in the therapeutic partnership. Angus Thompson describes how analogies and imagery can sometimes be useful to help patients understand the purpose of their medicines and the reasons behind treatment decisions.